IMPLEMENTASI GAYA KEPEMIMPINAN INSTRUKSIONAL DALAM PENINGKATAN RAPOR MUTU PENDIDIKAN SEKOLAH DI SDN 002 BALIKPAPAN SELATAN - Mita Elyana; Suyatno Suyatno; Ika Maryani (TEACHING : Jurnal Inovasi Keguruan dan Ilmu Pendidikan, 2026)
ABSTRACT Instructional leadership by school principals is a strategic approach to improving the quality of learning through strengthening teacher capacity, utilizing school data, and managing programs sustainably. This study aims to describe the implementation of instructional leadership by the school principal in improving Education Report Card outcomes and to identify its supporting and inhibiting factors at SDN 002 Balikpapan Selatan. The study employed a qualitative approach with a case study design. Data were collected through observation, in-depth interviews, and documentation involving the principal, teachers, and school personnel engaged in quality improvement programs. Data were analyzed using the Miles and Huberman interactive model through the stages of data collection, data reduction, data display, and conclusion drawing and verification, while data credibility was strengthened through source, technique, and time triangulation. The findings indicate that instructional leadership was implemented through the use of the Education Report Card in Data-Based Planning (PBD), continuous academic supervision, teacher professional development through In-House Training, learning communities, mentoring, and strategic school resource management. These practices were associated with improvements in Education Report Card indicators and the school's consecutive receipt of Performance-Based School Operational Assistance (BOS Kinerja) in 2023 and 2024. Supporting factors included school-wide collaboration, learning resources, funding support, and a positive school culture, while the main constraints involved differences in teacher competencies, limited time, and suboptimal follow-up of training. These findings emphasize the importance of data-based instructional leadership in sustaining school quality improvement. ABSTRAK Kepemimpinan instruksional kepala sekolah menjadi salah satu pendekatan strategis dalam mengarahkan peningkatan mutu pembelajaran melalui penguatan kapasitas guru, pemanfaatan data sekolah, dan pengelolaan program secara berkelanjutan. Penelitian ini bertujuan mendeskripsikan implementasi kepemimpinan instruksional kepala sekolah dalam meningkatkan capaian Rapor Pendidikan serta mengidentifikasi faktor pendukung dan penghambatnya di SDN 002 Balikpapan Selatan. Penelitian menggunakan pendekatan kualitatif dengan desain studi kasus. Data diperoleh melalui observasi, wawancara mendalam, dan dokumentasi yang melibatkan kepala sekolah, guru, serta personel sekolah yang terlibat dalam pelaksanaan program peningkatan mutu. Analisis data menggunakan model interaktif Miles dan Huberman melalui tahapan pengumpulan, reduksi, penyajian, serta penarikan dan verifikasi kesimpulan, sedangkan kredibilitas data diperkuat melalui triangulasi sumber, teknik, dan waktu. Hasil penelitian menunjukkan bahwa kepemimpinan instruksional diwujudkan melalui pemanfaatan Rapor Pendidikan dalam Perencanaan Berbasis Data (PBD), supervisi akademik berkelanjutan, pengembangan profesional guru melalui In House Training, komunitas belajar, pendampingan, serta pengelolaan sumber daya sekolah. Implementasi tersebut berkaitan dengan peningkatan indikator Rapor Pendidikan dan keberhasilan memperoleh BOS Kinerja pada 2023 dan 2024. Faktor pendukung meliputi kolaborasi warga sekolah, sumber belajar, pendanaan, dan budaya sekolah, sedangkan hambatannya berupa perbedaan kompetensi guru, keterbatasan waktu, dan tindak lanjut pelatihan yang belum optimal. Temuan ini menegaskan pentingnya kepemimpinan instruksional berbasis data untuk menjaga keberlanjutan peningkatan mutu sekolah.